Production of Struvite Fertilizer from Salt Pond Waste (Bittern) with The Aeration Process (Indonesian Journal of Chemical Science, 2024)
Salt production produces liquid waste known as "Bittern", which is a saturated solution containing minerals such as Magnesium, Sodium, Phosphorus and several other minerals. The mineral content in Bittern can be used as raw material for making Struvite fertilizer. Crystal formation Struvite can be done using the aeration method by injecting air into wastewater using an aerator. The process is carried out by mixing the three solutions containing the minerals Magnesium, Ammonium and Phosphate into a vertical reactor using a variation of NH4+ excess of 10%; 20%; 30%; 40%; 50% and varying the temperature by 30˚C; 40˚C; 50˚C; 60˚C; 70˚C. Both variables are run by flowing air at a rate of 1 L/minute and maintaining the pH to remain at pH 9. The process is stopped when the pH reaches 9. The precipitate formed will then be filtered and then carried out a drying process at room temperature. Next, the struvite crystals that have been formed will be analyzed using XRF and SEM methods. The best conditions are obtained at a temperature of 30℃ and an excess of NH4+ of 50%, namely with a Mg content of 15% and PO4 of 74.32%.